2012
DOI: 10.15208/pieb.2012.01
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign wealth funds in the globalization of financial markets

Abstract: This paper studies the investment funds with special emphasis on Sovereign Wealth Funds (SWFs), as new participants in the financial market. Considering that financial markets are one of the main carriers of globalization, our goal is to investigate development and the role of these investment funds with reference to contemporary theory and progressive practice of the market of developed countries. Although SWFs emerged in practice more than fifty years ago, they are not sufficiently explored in the theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Bortolotti, Fotak and Megginson (2013) argue that companies targeted by active SWFs tend to achieve an abnormal return over the long term, while companies targeted by passive SWFs tend to underperform. Dewenter, Han and Malatesta (2010) suggest that over a fi ve year investment horizon there exists mixed positive evidence on the relation between SWF ownership and the stock performance of targeted fi rms, which is consistent with Kotter and Lel's (2011) fi ndings of zero-returns over the long run. There are other papers, however, that have found that SWFs bring value to their target fi rms.…”
Section: Institutional Owners and The Financial Performance Of A Companymentioning
confidence: 55%
See 3 more Smart Citations
“…Bortolotti, Fotak and Megginson (2013) argue that companies targeted by active SWFs tend to achieve an abnormal return over the long term, while companies targeted by passive SWFs tend to underperform. Dewenter, Han and Malatesta (2010) suggest that over a fi ve year investment horizon there exists mixed positive evidence on the relation between SWF ownership and the stock performance of targeted fi rms, which is consistent with Kotter and Lel's (2011) fi ndings of zero-returns over the long run. There are other papers, however, that have found that SWFs bring value to their target fi rms.…”
Section: Institutional Owners and The Financial Performance Of A Companymentioning
confidence: 55%
“…For public pension funds, such relations were negative. Similarly Cornett, Marcus, Saunders and Tehranian (2007) fi nd a signifi cant relation between a company's operation cash fl ow returns and both the shareholding proportion and the number of investors, for those institutional investors less likely to have a business relationship with the fi rms. In a similar vein, the empirical fi nding of Yuan, Xiao and Zou (2008) suggest that equity ownership by mutual funds has a positive effect of fi rm performance.…”
Section: Institutional Owners and The Financial Performance Of A Companymentioning
confidence: 94%
See 2 more Smart Citations